Prawna definicja partnerstwa publiczno-prywatnego w Polsce = Legal definition of public-private partnership in Poland - Leśniak-Niedbalec, Nina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The scope of this article is the field of legal science. Its purpose is to familiarize the reader with the legal term "public-private partnership". The Polish Constitution does not define this term. On the other hand, the term included in the Act, amended a few times, still raises reservations. The author, using the language-logical method, performs a detailed analysis of this term. She also shows possible directions for the amendment of legal norms in the discussed subject-matter.
Keywords: partnerstwo publiczno-prywatne; administracja; samorząd terytorialny; public-private partnership; administration; local self-government